Dipeptidyl peptidase 4 expression is not associated with an activated fibroblast phenotype in idiopathic pulmonary fibrosis - Måns Kadefors; Frida Berlin; Marie Wildt; Göran Dellgren; Sara Rolandsson Enes; Anders Aspberg; Gunilla Westergren-Thorsson (Frontiers in Pharmacology, 2022)
Dipeptidyl peptidase 4 (DPP4) has been proposed as a marker for activated fibroblasts in fibrotic disease. We aimed to investigate whether a profibrotic DPP4 phenotype is present in lung tissue from patients with idiopathic pulmonary fibrosis (IPF). The presence of DPP4+ fibroblasts in normal and IPF lung tissue was investigated using flow cytometry and immunohistology. In addition, the involvement of DPP4 in fibroblast activation was examined in vitro, using CRISPR/Cas9 mediated genetic inactivation to generate primary DPP4 knockout lung fibroblasts. We observed a reduced frequency of primary DPP4+ fibroblasts in IPF tissue using flow cytometry, and an absence of DPP4+ fibroblasts in pathohistological features of IPF. The in vivo observations were supported by results in vitro showing a decreased expression of DPP4 on normal and IPF fibroblasts after profibrotic stimuli (transforming growth factor β) and no effect on the expression of activation markers (α-smooth muscle actin, collagen I and connective tissue growth factor) upon knockout of DPP4 in lung fibroblasts with or without activation with profibrotic stimuli.